2022
DOI: 10.1111/brv.12894
|View full text |Cite
|
Sign up to set email alerts
|

Integrative biology of injury in animals

Abstract: Mechanical injury is a prevalent challenge in the lives of animals with myriad potential consequences for organisms, including reduced fitness and death. Research on animal injury has focused on many aspects, including the frequency and severity of wounding in wild populations, the short‐ and long‐term consequences of injury at different biological scales, and the variation in the response to injury within or among individuals, species, ontogenies, and environmental contexts. However, relevant research is scat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 373 publications
0
25
0
Order By: Relevance
“…While there have been anecdotal notes on P. dumerilii’ s ability to regenerate its germline during posterior regeneration (Hauenschild and Fischer, 1969; Rebscher, 2014), systematic studies on this process to see whether removal and regeneration of germ cells have an impact on fertility and fecundity have not been carried out before. In some annelids injury can negatively impact reproduction, measured by the production of gametes, or gamete, cocoon, and brood numbers (Gibbs, 1968; Hill et al, 1982; Rennolds and Bely, 2023; Zajac, 1985). To address this in P. dumerilii , we implemented the most severe survivable amputation at three different developmental stages with differential germline investment states.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there have been anecdotal notes on P. dumerilii’ s ability to regenerate its germline during posterior regeneration (Hauenschild and Fischer, 1969; Rebscher, 2014), systematic studies on this process to see whether removal and regeneration of germ cells have an impact on fertility and fecundity have not been carried out before. In some annelids injury can negatively impact reproduction, measured by the production of gametes, or gamete, cocoon, and brood numbers (Gibbs, 1968; Hill et al, 1982; Rennolds and Bely, 2023; Zajac, 1985). To address this in P. dumerilii , we implemented the most severe survivable amputation at three different developmental stages with differential germline investment states.…”
Section: Discussionmentioning
confidence: 99%
“…Injury is generally expected to have an energetic cost and consequently a negative effect on growth and reproduction outputs such as reduced fecundity, lower egg numbers, smaller egg size, or longer time to sexual maturation (Olive and Clark, 1978; Rennolds and Bely, 2023). Regenerating sponges and corals may have reduced fecundity or may remain infertile (Henry and Hart, 2005) due to resource trade-offs between regeneration and sexual reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…impaired immune system, degenerative cell destruction) than merely depleted energy reserves. Following a mechanical injury, reproduction is commonly reduced in favour of regeneration in a wide range of species (Rennolds & Bely, 2023). Accounting for a trade-off between damage and reproduction can dramatically change the predictions of life-history models: using this approach, showed that the classical prediction that organisms should invest increasingly in reproduction as they approach the end of their life (e.g.…”
Section: Trade-offs In Adaptive Behaviourmentioning
confidence: 99%
“…These two traits often co‐occur in soft‐bodied taxa like cnidarians, planarians, and annelids (Berrill, 1952; Brockes & Kumar, 2008; Giangrande & Licciano, 2014; Kostyuchenko & Kozin, 2020; Zattara & Bely, 2016). Given the prevalence of injury in wild populations of these groups (Lindsay, 2010; Rennolds & Bely, 2023), allocation strategies involving regeneration and reproduction (whether sexual or asexual) are ecologically relevant and likely have been shaped strongly by natural selection. Both processes require resource investment, leading to short‐ and possibly long‐term physiological and higher‐order consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Both processes require resource investment, leading to short‐ and possibly long‐term physiological and higher‐order consequences. The costs of both traumatic loss of a body part and its subsequent regeneration can be wide‐ranging and significant (Bely, 2010; Bernardo & Agosta, 2005; Lawrence, 2010; Maginnis, 2006; Rennolds & Bely, 2023). A considerable amount of research has investigated the effects of injury and regeneration on sexual reproduction.…”
Section: Introductionmentioning
confidence: 99%